A layered Ge2Sb2Te5 phase change material. Issue 5 (27th January 2020) - Zhang, Bo; Cicmancova, Veronika; Kupcik, Jaroslav; Slang, Stanislav; Rodriguez Pereira, Jhonatan; Svoboda, Roman; Kutalek, Petr; Wagner, Tomas
Abstract : In this study, a universal Ge2 Sb2 Te5 phase change material was sputtered to obtain a layered structure. Abstract : In this study, a universal Ge2 Sb2 Te5 phase change material was sputtered to obtain a layered structure. The crystalline phase of this material was prepared by annealing. SEM (scanning electron microscopy) and HRTEM (high-resolution transmission electron microscopy) images give confirmed that the sputtered Ge2 Sb2 Te5 thin film in crystalline phase has multiple layers. The layers can be exfoliated by acetone. The thicknesses of acetone-exfoliated crystalline and amorphous flakes are approx. 10–60 nm.